The professional culture among physicians in Sweden: potential implications for patient safety - Marita Danielsson; Per Nilsen; Hans Rutberg; Siw Carlfjord (BMC, 2018)
Abstract Background Patient safety culture, i.e. a subset of an organization's culture, has become an important focus of patient safety research. An organization's culture consists of many cultures, underscoring the importance of studying subcultures. Professional subcultures in health care are potentially important from a patient safety point of view. Physicians have an important role to play in the effort to improve patient safety. The aim was to explore physicians' shared values and norms of potential relevance for patient safety in Swedish health care. Methods Data were collected through group and individual interviews with 28 physicians in 16 semi-structured interviews, which were recorded and transcribed verbatim before being analysed with an inductive approach. Results Two overarching themes, "the competent physician" and "the integrated yet independent physician", emerged from the interview data. The former theme consists of the categories Infallible and Responsible, while the latter theme consists of the categories Autonomous and Team player. The two themes and four categories express physicians' values and norms that create expectations for the physicians' behaviours that might have relevance for patient safety. Conclusions Physicians represent a distinct professional subculture in Swedish health care. Several aspects of physicians' professional culture may have relevance for patient safety. Expectations of being infallible reduce their willingness to talk about errors they make, thus limiting opportunities for learning from errors. The autonomy of physicians is associated with expectations to act independently, and they use their decisional latitude to determine the extent to which they engage in patient safety. The physicians perceived that organizational barriers make it difficult to live up to expectations to assume responsibility for patient safety. Similarly, expectations to be part of multi-professional teams were deemed difficult to fulfil. It is important to recognize the implications of a multi-faceted perspective on the culture of health care organizations, including physicians' professional culture, in efforts to improve patient safety.